2016
DOI: 10.5194/acp-16-6131-2016
|View full text |Cite
|
Sign up to set email alerts
|

Inter-comparison of stratospheric mean-meridional circulation and eddy mixing among six reanalysis data sets

Abstract: Abstract. The stratospheric mean-meridional circulation (MMC) and eddy mixing are compared among six meteorological reanalysis data sets: NCEP-NCAR, NCEP-CFSR, ERA-40, ERA-Interim, JRA-25, and JRA-55 for the period 1979-2012. The reanalysis data sets produced using advanced systems (i.e., NCEP-CFSR, ERA-Interim, and JRA-55) generally reveal a weaker MMC in the Northern Hemisphere (NH) compared with those produced using older systems (i.e., NCEP/NCAR, ERA-40, and JRA-25). The mean mixing strength differs largel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 79 publications
4
20
0
Order By: Relevance
“…However, these modeled trends have proven hard to detect in the real atmosphere: For instance, insignificant trends in AoA have been reported from long‐lived tracer observations in the boreal midlatitude stratosphere (e.g., Engel et al, , ). In recent years, however, new studies have found evidence supporting a residual circulation acceleration in the lower stratosphere based on long‐term temperature and tracer observations (e.g., Hegglin et al, ; Ray et al, ; Young et al, ), as well as reanalysis data sets (Abalos et al, ; Miyazaki et al, ). The difficulty in deriving BDC trends can be partly attributed to limited spatial and temporal sampling of the observations, along with the large internal variability in the strength of this circulation (e.g., Garcia et al, ; Garfinkel et al, ; Hardiman et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, these modeled trends have proven hard to detect in the real atmosphere: For instance, insignificant trends in AoA have been reported from long‐lived tracer observations in the boreal midlatitude stratosphere (e.g., Engel et al, , ). In recent years, however, new studies have found evidence supporting a residual circulation acceleration in the lower stratosphere based on long‐term temperature and tracer observations (e.g., Hegglin et al, ; Ray et al, ; Young et al, ), as well as reanalysis data sets (Abalos et al, ; Miyazaki et al, ). The difficulty in deriving BDC trends can be partly attributed to limited spatial and temporal sampling of the observations, along with the large internal variability in the strength of this circulation (e.g., Garcia et al, ; Garfinkel et al, ; Hardiman et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Abalos et al (2015) have recently compared the stratospheric Brewer-Dobson circulation among MERRA, ERA-I, and JRA55, while Miyazaki et al (2016) did a somewhat similar study with six different reanalyses. Abalos et al (2015) find quite large (∼ 40 %) differences among the reanalyses in the overall strength of the BD circulation and a large spread among the estimates of the fraction of variance in mean vertical motion explained by the QBO.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…We have also restricted our attention to the period starting in 1979 when NOAA operational satellite radiance observations became available and were incorporated as an important data source in all the reanalyses. We appreciate that other aspects of the reanalyses in this region are also of interest, notably the ability of the reanalyses to represent accurately the large-scale transport circulation in the stratosphere (e.g., Coy and Swinbank, 1997;Abalos et al, 2015;Miyazaki et al, 2016), but these aspects will be left for future research.…”
Section: Introductionmentioning
confidence: 99%
“…They noted good agreement in the diagnostics after 2002, but cautioned that the choice of one over the other could influence the results of polar processing studies. Miyazaki et al (2016) intercompared six reanalyses (R1, ERA-40, JRA-25, CFSR, ERA-I, JRA-55) to study the mean meridional circulation in the stratosphere and eddy mixing and their implications upon the strength of the Brewer-Dobson circulation. Fujiwara et al (2015) used nine reanalyses (JRA-55, MERRA, ERA-I, CFSR, JRA-25, ERA-40, R1, R2, and 20CR) to examine their stratospheric temperature response to the eruptions of Mount Agung (1963), El Chichón (1982, and Mount Pinatubo (1991).…”
Section: Introductionmentioning
confidence: 99%